PERSEPSI UMAT MUSLIM GENERASI Z TERHADAP UMAT KRISTIANI DALAM RANGKA PENCEGAHAN KONFLIK KEAGAMAAN - Aulia, Guruh Ryan; Rahman, Magfirah; Wardi, Syah (Islamijah: Journal of Islamic Social Sciences, 2025)
This article investigates how Generation Z Muslims view Christians, with the aim of preventing religious conflict in Indonesia's diverse society. Generation Z, who live in a digital and multicultural era, have broad access to information and religious social interactions that influence their views on diversity. This article uses a qualitative approach and in-depth interviews, and reveals that most Generation Z Muslims show positive attitudes towards Christians, as seen in the values of brotherhood, tolerance, and religious moderation. Christians are seen as an equal segment of Indonesian society, who uphold human values and do not interfere with the religious practices of Muslims. These values, which are rooted in Islamic teachings such as Surah Al-Kafirun verse 6, play an important role in preventing religious conflict. Generation Z Muslims have significant potential to act as agents of peace and promote inclusive community development. Therefore, interfaith education and the strengthening of multicultural values in higher education need to be improved.